A randomized controlled trial of comparative effectiveness of elastic therapeutic tape, sham tape or eccentric exercises alone for lateral elbow tendinosis. (December 2016) - Wegener, Raewyn L; Brown, Ted; O'Brien, Lisa
Introduction: Lateral elbow tendinosis is a condition that is well known to cause difficult challenges for hand therapists due to its long-term recovery and morbidity. Elastic therapeutic tape is commonly used as a treatment modality, despite limited evidence. Methods: A randomized controlled trial was conducted to evaluate the effectiveness of elastic therapeutic tape, in conjunction with eccentric exercises, in the treatment of lateral elbow tendinosis. Forty participants with this condition (12 men, 28 women) were randomly allocated to three groups: (i) elastic therapeutic tape and eccentric exercises, (ii) sham tape and eccentric exercises, and (iii) eccentric exercises alone. All groups received education on activity modification techniques. Interventions were undertaken over a 12-week period (four weekly sessions and four fortnightly sessions) and outcome measures were recorded at baseline, three months and six months post randomisation. Results: At three and six months, improvements were made in all three groups as assessed with the Patient-Rated Tennis Elbow Evaluation, the Short Form 36, pain-free grip strength, and the Occupational Self Assessment. However, there were no statistically significant differences between groups in any of these measures. There were no significant side effects or symptom exacerbation with using the elastic therapeutic tape. Conclusions: Whilst all groups improved on key outcomes, it is possible that exercise alone and/or natural recovery were responsible for improvements. It is positive to note that the use of elastic therapeutic tape was well tolerated by participants and not associated with any significant side effects or symptom exacerbation.